View of the Vedibandha of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The closer view of the vedibandha (basal mouldings) of the Undeshwar Temple shows the gajathara moulding (elephants in the band). This moulding is commonly found in grand Bhumija temples. The kumbha (pot) moulding is adorned with miniature niches containing figures of deities. The kalasha (pitcher) molding is also intricately carved with a band featuring a diamond motif.